Surgical management of hemorrhagic pancreatic pseudocyst with splenic artery rupture and submucous hematoma of gastric wall development - Sergeevich, Belyuk Konstantin; Aleh Stanislovovich, Soroka; Yaroslaw Michailowicz, Zhuk; Wattaladeniya, Poorna Gayan; Varsha Priyadarshani, M. G. W .M.; Gunarathna, K. D. Ishara Nadeeshani; Rosa, Sellappulige Sadul Visvajith; Segarajasingam, Akshayan (International Surgery Journal, 2025)
Hemorrhagic pancreatic pseudocyst is a rare but life-threatening complication of chronic pancreatitis due to the erosion of vascular vessels by leakage of pancreatic enzymes. This case report aims to highlight the diagnostic challenges, investigation methods, and management strategies for hemorrhagic pancreatic pseudocysts while emphasizing the importance of a multidisciplinary approach. 47-year-old male presented with chronic pancreatitis presented with severe abdominal pain and gastrointestinal bleeding. Investigations included ultrasonography, gastrography with barium swallow study, endoscopy, CT and MRI, which revealed a hemorrhagic pseudocyst eroding the gastric mucosa. Celiacography identified splenic artery rupture, leading to initial management through endovascular embolization using nitinol spirals. However, recurrent bleeding necessitated surgical intervention. Laparotomy revealed a massive hemorrhagic pancreatic pseudocyst invading the gastric mucosa and the patient underwent an en-bloc resection of the proximal part of the stomach with hemorrhagic pseudocyst, and distal resection of pancreas with splenectomy followed by esophagogastrostomy. After proper surgical intervention, patient showed improvement. Post-operative complications including subdiaphragmatic abscess and pleural effusion were managed with surgical drainage and thoracocentesis and antibiotics. The patient gradually improved, and was discharged in a satisfactory condition. This case highlights the importance of early diagnosis through advanced imaging studies and timely intervention using radiological, endovascular and surgical techniques. Although embolization provides a temporary hemostasis, definite surgical intervention is required in cases of vascular destruction and pseudo cyst ruptures invading the surrounding tissues.